Effects of applying SC27 microbial soil fertility intensifier on “Kyoho” grapevines - YU Dan-hong; HUANG Jing-fa; HUANG Chang-yong (浙江大学学报. 农业与生命科学版)
The effects of SC27 microbial soil fertility intensifier on growth, yield and quality of “Kyoho” grapevines were studied. It was shown that growth of grapevines was promoted and fruit yield per unit area was increased by 10.1%-22.0% as a consequence of SC27 application. In addition, SC27 apparently improved grape quality due to increased amount of soluble solid substances, higher vitamin C and total sugar content, as well as higher sugar to acid ratio and soluble solid substance to acid ratio. According to our experimental results, the optimal dosage of SC27 for grapevines was 1050 mL/hm2 repeatedly applied 3 times during one growth period.